An anaplastic lymphoma kinase (ALK) fusion oncogene positive metastatic sarcomatoid carcinoma of the lung with good response to crizotinib - Valter, Ann; Roosipuu, Retlav; Tamm, Hannes; Padrik, Peeter (AME Case Reports, 2018)
Primary sarcomatoid carcinoma (SC) of the lung is a rare tumor that accounts for less than 1% of all lung cancers and compared to other non-small cell lung cancers (NSCLC) they appear more aggressive with poorer prognosis and response to treatment. Carcinosarcoma is one of the subtypes of SC. We report a case of carcinosarcoma with ALK-EML4 fusion gene in a 50-year-old male patient with a good response to therapy with crizotinib. An ALK rearrangement is a rare finding in SC, but as this case demonstrates, it may occur and it is necessary to perform the ALK testing in these tumors to find possible targeted treatments for better outcomes.